MacDonald, Martha. Dale Jarvis interviews Martha MacDonald, Associate Director, Education and Training, Labrador Institute of Memorial University, Happy Valley-Goose Bay, Labrador, 25 November 2010. - Jarvis, Dale (2010)
Dale Jarvis interviews Martha MacDonald, Associate Director, Education and Training, Labrador Institute of Memorial University, Happy Valley-Goose Bay, Labrador, 25 November 2010. MacDonald explains what is meant in Labrador by the term "mug up"; describes the development of a community story exchange program called "Mug Ups"; how the program evolved; tips for communities who want to start their own Mug Up-style project; the importance of having a set topic for the conversations; the importance of having transportation for community elders and seniors; example of a Mug Up conversation around summer and winter housing in Mary's Harbour; and CBC Radio involvement in the project.